Thermal performance of casson hybrid nanofluid with radiative effects and convective conditions: applications to energy systems and industrial heat transfer - Ishaq, Manzoor; Khan, Sami Ullah; Garalleh, Hakim AL; Sowayan, Ahmed S.; Tlili, Iskander (Multiscale and Multidisciplinary Modeling, Experiments and Design, 2025)
This analysis provides insight into optimizing the thermal management in industrial heat transfer and energy systems with applications of Casson hybrid nanofluid. By including the radiated features and convective boundary constraints, this investigation discloses the efficiency enhancement for thermal systems, including the heat exchangers and solar collectors. The suspension of hybrid nanofluid containing the gold Au and silver Ag nanoparticles with blood base fluid. The heat equation is updated with implementation of Cattaneo-Christov approach. A moving configuration is assumed to induces the flow subject to porous media. Thermal aspects of hybrid nanofluid to improve the heat transfer phenomenon has been studied with important thermo-physical properties. Thermal dynamic of problem is captured with help of differential equations for which numerical simulations are performed via shooting scheme. Comparative thermal observations for hybrid nanofluid and mono nanofluid has been performed subject to various of different flow parameters. Moreover, numerical simulations and graphical analysis for skin friction and Nusselt number has been performed. The concluded observations support advancements in various industrial cooling systems, where the improved heat transfer attributes novel role in the operational stability and equipment longevity. It has been observed that change in Biot number and presence of heat generation improve the heat transfer phenomenon, with implications for thermal management systems. Both mono and hybrid nanomaterials demonstrate the enhanced thermal efficiency with larger nanoparticles volume faction. The skin friction declined due to Darcy parameter and Hartmann number. Moreover, the hybrid nanofluids show more efficient thermal performance as compared to mono nanofluid.